Strategies for Paint Waste Minimization in the Packaging Industry - Ari Dina Permana Citra; Purwanto Purwanto (Diponegoro University, 2020)
Cosmetic packaging painting using an alkyd resin compound is to make a smooth, glossy surface and attract the attention of consumers. The generated waste is handed over to a third party and has not been utilized as a product, so it requires a high enough cost. This research aims to develop a waste management strategy from its source to its utilization into a product. The research method uses a block diagram of the production process to identify waste generation and opportunities for prevention and reduction. Waste arising from alternative uses is created into a product leading to zero waste. This approach provides economic and environmental benefits for the cosmetics packaging industry.